Intentional practice: a common language, approach and set of methods to design, adapt and implement contextualised wellbeing solutions - Raymond, Ivan J. (Frontiers in Health Services, 2023)
Reducing the “science-to-practice” gap has gained significant attention across multi-disciplinary settings, including school psychology and student wellbeing, trauma-informed practice, community and human services, and clinically focused health care. There has been increasing calls for complexity and contextualisation to be integrated within the implementation science literature. This includes the design and implementation of interventions spanning “systems” (whole-of-community capacity building initiatives), “programs” (e.g., evidence-based programs, clinical interventions) and “moment-to-moment” support or care. The latter includes responses and communication designed to deliver specific learning, growth or wellbeing outcomes, as personalised to an individual’s presenting needs and context (e.g., trauma-informed practice). Collectively this paper refers to these interventions as “wellbeing solutions”. While the implementation science literature offers a range of theories, models and approaches to reduce the science-to-practice gap in wellbeing solution design and implementation, they do not operationalise interventions into the “moment”, in a manner that honours both complexity and contextualisation. Furthermore, the literature’s language and content is largely targeted towards scientific or professional audiences. This paper makes the argument that both best-practice science, and the frameworks that underpin their implementation, need to be “sticky”, practical and visible for both scientific and non-scientific knowledge users. In response to these points, this paper introduces “intentional practice” as a common language, approach and set of methods, founded upon non-scientific language, to guide the design, adaptation and implementation of both simple and complex wellbeing solutions. It offers a bridge between scientists and knowledge users in the translation, refinement and contextualisation of interventions designed to deliver clinical, wellbeing, growth, therapeutic and behavioural outcomes. A definitional, contextual and applied overview of intentional practice is provided, including its purported application across educational, wellbeing, cross-cultural, clinical, therapeutic, programmatic and community capacity building contexts